Conflict management styles of the educational administrators in Universiti Teknologi MARA Sarawak in dealing with subordinates / Aiza Johari … [et al.] - Johari, Aiza; Morni, Affidah; Ahmad, Johnny; Abg Bohari, Dayang Faridah (2009)
The paper presented the findings of a survey to identify the possible causes of conflicts that might arise when the Heads of Academic Programme and Programme Coordinators were dealing with the subordinates at the workplace (UiTM Sarawak), the effects of such conflicts and their conflict management styles. 23 subjects took part in the survey. Generally, the findings indicated that many of the respondents did not face many problems in the six possible areas of conflicts as shown by the positive responses to the related questions. From the findings, it was gathered that the Heads of Programme and Coordinators had carried out their responsibilities well as leaders by practising effective communication, conducting efficient coordination and organization, respecting the different personalities of their subordinates, applying positive leadership styles and showing high commitment and collaboration. The findings also revealed that most superiors had faith in their subordinates as they believed that their subordinates would still maintain their professionalism in the face of conflicts. Thus, conflicts were not perceived as mainly negative which hindered work progress, but as challenges that would achieve higher work productivity. As far as the conflict resolution (conflict management styles) is concerned, the majority of the respondents preferred the collaborative style which focuses on collaboration and cooperation, thus creating a harmonious working environment, and decreasing possible conflicts.